Pengaruh Corporate Governance, Firm Age, Dan Ownership Structure Terhadap Earning Management - Maulidya Rahma Syafira, Nurainun Bangun (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study was to determine the effect of corporate governance, firm age, and ownership structure on earnings management. The population used is a company engaged in manufacturing which is listed on the Indonesia Stock Exchange (IDX) website, with a research period from 2016-2018. This research uses purposive sampling method with predetermined criteria. Earning management is calculated using the discretionary accruals method. The results of this study stated that corporate governance with an independent commissioners proxy had no significant negative effect on earnings management, firm age had a significant positive effect on earnings management, and ownership structure with a proxy for public ownership had a significant negative effect on earnings management.